2015
DOI: 10.1055/s-0035-1549217
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Genetic Variation in Steroid Metabolism and Key Respiratory Function Genes and Perinatal Outcomes in Single and Multiple Courses of Corticosteroids

Abstract: OBJECTIVE-To evaluate the association of steroid metabolism and respiratory gene polymorphisms in neonates exposed to antenatal corticosteroids (ACS) with respiratory outcomes, small for gestational age (SGA) and response to repeat ACS.STUDY DESIGN-This candidate gene study is a secondary analysis of women enrolled in a randomized controlled trial of single versus weekly courses of ACS. Nineteen single nucleotide polymorphisms (SNPs) in 13 steroid metabolism and respiratory function genes were evaluated. DNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In small for gestational age infants, these SNPs have been associated with differences in the reduction in RDS 25 . Clinical data suggests that the effect of antenatal sGC therapy is limited in intrauterine growth restricted fetuses (IUGR) and that ‘it remains unclear if ACS therapy is beneficial due to heterogeneous populations and treatment regimes’ 26 .…”
Section: Demographic Variables In the Response To Antenatal Sgc Therapymentioning
confidence: 99%
“…In small for gestational age infants, these SNPs have been associated with differences in the reduction in RDS 25 . Clinical data suggests that the effect of antenatal sGC therapy is limited in intrauterine growth restricted fetuses (IUGR) and that ‘it remains unclear if ACS therapy is beneficial due to heterogeneous populations and treatment regimes’ 26 .…”
Section: Demographic Variables In the Response To Antenatal Sgc Therapymentioning
confidence: 99%
“…CRHBP has been investigated in the field of normal physiologic, metabolic function and oncogenesis ( 12 , 13 ). It was reported that Caucasians and African Americans with low CRHBP expression were associated with an increased risk of breast cancer ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of genetic variation in CRHR1 to corticosteroid response has been described in Chronic Obstructive Pulmonary Disease (COPD)(27) asthma(12) and persistent pulmonary hypertension of the newborn(28). Genetic variation in the ligand for CRHR1 , corticotropin releasing hormone (CRH), is associated with neonatal respiratory response to maternal prenatal corticosteroid therapy (10). Fetuses who carry the risk allele at rs7225082 are more likely to require CPAP/ventilator postnatally (poor response to maternal corticosteroids) and correspondingly in our study, preterm infants who carry the risk allele have a poorer response to postnatal corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Variant alleles can influence drug metabolism, disposition and drug target sensitivity, and explain some of the heterogeneity in efficacy and toxicity that is observed within a patient population. A recent study (10) links neonatal genetic variation to respiratory phenotype at birth after maternal treatment with antenatal corticosteroids. In asthma, multiple single nucleotide polymorphisms (SNPs) in corticosteroid metabolism and response genes modify clinical response to inhaled corticosteroids(11-17).…”
Section: Introductionmentioning
confidence: 99%